METODE BIBLIOTHERAPY PADA KISAH NABI YUSUF AS SEBAGAI MEDIA KONSELING RASIONAL EMOTIF - Neni Noviza (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2013)
Bibliotherapy is an expressive therapy in which there is an individual relationship with the content or essence books , poems and other writings as a therapy . Bibliotherapy according to experts is one type of therapy that uses the activity of reading a piece of literature to address the problems faced by a person . Bibliotherapy assignments include reading to reading materials selected , planned , and directed as a procedure with the aim of therapeutic action . With bibliotherapy is believed to influence the attitudes , feelings , and behaviors of individuals as expected and may stimulate readers to think . Bibliotherapy easy to implement , inexpensive , and can be done anytime and involves the reader 's own self-sufficiency and full participation to internalize it . Provision of treatment need to be disseminated in the form of bibliotherapy as a method of meaningful action .Bibliotherapy in the story of Prophet Yusuf as very appropriate to be used as a medium of rational emotive counseling in changing pemikiraan irrational becomes rational thinking person that reflected the emotions and behavior in both in family life , school , and community environments . Surah Yusuf called by the Almighty as ahsanul qasasi ( most good stories ) , because it contains a lot of ' ibrah (lessons ) for people who have sense. Allah the Exalted says ,